PTV measurement and DEM simulation of the particle motion in a flighted rotating drum - Zhang, Lanyue; Jiang, Zhaochen; Weigler, Fabian; Herz, Fabian; Mellmann, Jochen; Tsotsas, Evangelos (Powder Technology, 2020)
To investigate the particle motion in the flighted rotating drum (FRD), a laboratory drum with four rectangular flights is horizontally arranged and filled with plastic particles in this work. The FRD is operated by varying the drum rotating speed (10, 20, and 30 rpm) and filling degree (10, 15, and 20%). The particle tracking velocimetry (PTV) method and DEM simulation (with LIGGGHTS software) are applied to analyze the particle movements. The results have shown that, as the drum rotating speed is increased, the holdup ratio and cascading rate of an individual flight increase. The drum rotating speed also affects the particle ratios in three phases and the falling time distribution of the dilute phase. Moreover, the average velocities and granular temperatures of the particle system in FRD increase as the drum rotating speed increases and the filling degree decreases. Good agreements are observed between the PTV measurements and DEM simulations.
CRIS-Team Scopus Importer:2020-01-21
Keywords: DEM; Flighted rotating drum; Granular temperature; Particle motion; Particle velocity; PTV